IMPACT OF ORGANIZATIONAL IDENTIFICATION ON THE PERFORMANCE OF FACULTY MEMBERS, EVIDENCE FROM JORDANIAN UNIVERSITY (Journal of Pharmaceutical Negative Results, 2023)
This study aims to identif the organizational identification dimensions (loyalty, similarity and membership) and its impact on the performance of faculty members at Isra University/Jordan, in order to expand knowledge in this field, descriptive analysis and statistics methods have been applied for this research. The study population consisted of all faculty members working at Isra University (236) members. The study sample consisted of (170) members,(153) questionnaires received and subjected to statistical analysis, the result showed that the attitudes of the study sample towards the level of organizational identification at Al-Isra University are positive with high degree, and the attitudes of the study sample towards the performance level of the faculty members are positive and high. In addition, there is a statistically significant impact of organizational identification (similarity and membership) on the performance of the faculty members, and there is no significant impact of organizational identification (loyalty) on the performance of the faculty members. The study recommended strengthening the faculty members affiliation with their university, and the university administration works to achieve the conformity of the goals of the faculty member with his university, also the university administration offers better benefits to faculty members, and improving their incentives, salaries and wages.